EFICÁCIA NA PRESTAÇÃO JURISDICIONAL EM COMARCAS TRANSFRONTEIRIÇAS SUL-MATO-GROSSENSES: Mulheres migrantes vítimas de violência doméstica - minoria multivulnerável. ODS nº 5 e 16 ONU - Erika Arevalo da Rosa (2021)
ABSTRACT The objective of the research is to describe the jurisdictional provision provided in the crossborder regions of Mato Grosso do Sul to migrant women victims of domestic violence. To achieve it, three studies were carried out. The first consists of a theoretical essay that sought to review the bibliography on the themes: gender and domestic violence, borders, migration and human rights; the second quantitatively investigated the jurisdictional production in the counties with the headquarters of neighboring municipalities and the third sought to identify some predictor variables, especially with regard to the effectiveness of the jurisdictional provision offered to the multi-vulnerable minority studied. The focus is on the first instance of the State Court, because in this segment more than two thirds of all pending lawsuits in the country are concentrated. Secondary data were collected from the automation system of the Court of Justice of Mato Grosso do Sul (TJMS) for the year 2018. The results showed that the jurisdictional provision offered to migrant women who suffered domestic violence, in the period analyzed, was, in its majority, deficient, focused on the punitive system and the figure of the aggressor, leaving the victim completely forgotten. Analysis of statistical data also revealed that quantitative performance in cross-border counties was predominantly low and the judiciary service time-consuming. At the end of the research, the findings found in the investigated services were presented. Keywords: gender, domestic violence, cross-border counties, migrant women, multivulnerable minority groups, human rights.